A qualitative study of care coordination in community physical rehabilitation. (September 2019) - Symons, Jane L; Jamison, Julie; Dening, Jane; Murray, Linda; Pearson, Sue
Introduction: This study explored the factors influencing effective care coordination in a community physical rehabilitation service. The two research questions answered were "What was effective care coordination?" and "What were the barriers and enablers?" Methods: This qualitative study, influenced by an interprofessional skill framework, was conducted in a regional service in Australia. Participants were 35 allied health, nursing, and client administration team members. Individual interviews, group observations, and focus groups generated data. This article will present the descriptive thematic analysis method and results. Results: Care coordination resulted from a suite of informal and formal tools that smoothed the client's rehabilitation journey. Effectiveness and efficiency were sought alongside client-centred, holistic, and flexible yet consistent approaches to care coordination. All staff undertook care coordination relevant to their managerial, clinical, or administration support roles. The involvement of many people and processes required effective teamwork, notably communication, collaboration, coordination, and navigation of stakeholder differences. The barriers to and enablers of care coordination were the service's resources including integrated workspaces, transport and communication systems, and the individuals' resources including clinical reasoning skills in, and familiarity and buy in with care coordination and rehabilitation. Discussion: Staff viewed care coordination as an integral and valued part of rehabilitation, with some responsibilities shared by all staff. Additional time and support were required for stakeholders to enact their assigned care coordination roles. Effective care coordination required staff to be trained and competent in interprofessional collaboration. Systems that were efficient to use and encouraged accountability were desired.